Perirhinal cortex ablation impairs configural learning and paired-associate learning equally. - Buckley, M; Gaffan, D (1998)
Combined damage to the perirhinal and entorhinal cortex has been implicated in the formation of stimulus-stimulus associative memories. We show in this article that relative to three normal controls three cynomolgus monkeys with ablations restricted to the perirhinal cortex were impaired on a visual paired associate learning task in which subjects had to learn which of two visual stimuli were associated with a cue stimulus. The subjects with perirhinal cortex ablations also showed an impairment of a similar magnitude on a visual configural learning task in which they had to learn which of two configurations of visual stimuli were associated with food-reward. The stimuli in both tasks were comprised of alphanumeric characters presented upon a touch-screen. Both groups made fewer errors on the configural learning task than on the paired associate learning task. We suggest that performance on both tasks relies critically on the perirhinal cortex due to the specialization of the perirhinal cortex in processing knowledge about objects. We argue that the specializations of this system and of other memory systems such as the hippocampal-fornix spatial/episodic memory system, are conferred by the specialization of their anatomical connections to other structures. We reject the notion that there are specific memory processes such as the hippocampal based configural associative system that was proposed to be critical for configural associative learning.